Evaluación de 2 variedades de pimiento con la aplicación de té de estiércol animal (heces bovinas y gallinaza) como fertilizante, en la ciudad de Ibarra provincia de Imbabura - Ibarra Carlosama, Juan Daniel (2022)
Pepper cultivation has had a great impact in recent years, being one of the most consumed products worldwide, which has caused an increase in its production and export in Ecuador. The objective of this research was to evaluate the results of the use of animal manure tea (bovine manure and chicken manure) against chemical fertilization in the cultivation of two varieties of pepper (Nathalie and Marly), in the Ibarra city, Imbabura. province Through field evaluations, it was determined which variety presented a better agronomic behavior with the use of manure tea. The experiment was carried out at the experimental farm of the School of Agricultural and Enviromental Sciences of the Pontificia Universidad Católica del Ecuador Sede Ibarra, with an experimental design of DCA with AxB factorial arrangement, by means of the Rstudio program, the comparative analyzes were carried out with the Tukey test at 5%. Obtaining the following results: in the height variable at 30 days there are significant differences for T2 (Var. Nathalie with chicken manure tea) with 35,93 cm, but when reaching flowering the most distinctive heights have T1 (Var. Nathalie with chemical fertilizer) and T3 (Var. Nathalie with bovine manure tea) with 48,87 and 47,7 cm respectively. In the phenological development, it can be observed that the Marly R variety reaches flowering 1,71 days before Nathalie variety, but in the fruiting stage there is no significance in any of the factors. In fruit quality, significant results can be seen with treatment 5 (Marly R variety with chemical fertilizer), presenting a fruit weight and length of 97,51g 13,85cm, but no differences were found in the fruit caliber results. In the number of fruits harvested per plant, a higher number was reached with bovine manure tea, with 4,57 fruits harvested per plant. For the total yield, the projection generated with T3 (Nathalie variety and with bovine manure tea) was higher than the other treatments with 43,098.96 kg ha-1, for which it is determined that manure tea can be used. bovine as an alternative substitute for chemical fertilizer, it was also observed that the Natalie variety has a better productive index in the área.